Pediatric Neurotrauma - Kannan, Nithya (Medknow Publications & Media Pvt Ltd, 2014)
Traumatic brain injury (TBI) is the leading cause of death and disability in children over 1 year of age. Knowledge about the age-specific types of injury and how to manage children with neurotrauma is essential to understanding and recognizing the extent and degree of injury and to optimize outcomes. In this article, we review the epidemiology, pathophysiology, and clinical management of pediatric neurotrauma.